General hardening of children - Gulrukh Shahbazova (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article highlights the importance of using the healing powers of nature wisely so that preschool children can grow up physically and mentally fit and healthy. It also details the practical method of training young children through air and sun baths.